Filopodia-based contact stimulation of cell migration drives tissue morphogenesis. - Bischoff, M.C.; Lieb, S.; Renkawitz-Pohl, R.; Bogdan, S. (Nature communications, 2021)
Cells migrate collectively to form tissues and organs during morphogenesis. Contact inhibition of locomotion (CIL) drives collective migration by inhibiting lamellipodial protrusions at cell-cell contacts and promoting polarization at the leading edge. Here, we report a CIL-related collective cell behavior of myotubes that lack lamellipodial protrusions, but instead use filopodia to move as a cohesive cluster in a formin-dependent manner. We perform genetic, pharmacological and mechanical perturbation analyses to reveal the essential roles of Rac2, Cdc42 and Rho1 in myotube migration. These factors differentially control protrusion dynamics and cell-matrix adhesion formation. We also show that active Rho1 GTPase localizes at retracting free edge filopodia and that Rok-dependent actomyosin contractility does not mediate a contraction of protrusions at cell-cell contacts, but likely plays an important role in the constriction of supracellular actin cables. Based on these findings, we propose that contact-dependent asymmetry of cell-matrix adhesion drives directional movement, whereas contractile actin cables contribute to the integrity of the migrating cell cluster.